The Spirit of Al-Gazali against Capitalism in Pandemic Covid-19 Era - Muhammad Ismail; Muhammad Majdy Amiruddin; M Ali Rusdi; M Ilham (Al-Izzah: Jurnal Hasil-Hasil Penelitian, 2021)
Capitalist behavior was unavoidable when the co-19 outbreak struck. Panic buying at a number of shopping centers, as well as hoarding of healthcare supplies such as masks and sanitizers, are all manifestations of capitalism’s selfish behavior. This essay stressed the critical importance of ethics in all parts of behavior, including economic activity, in order to dissuade such behavior. This study took a qualitative method, with Al-Gazali’s Sufistic thinking serving as the primary reference point. This study took a sociological perspective. The primary data collection took place over the course of one week at Lakessi traditional market, Sejahtera store, Alfamidi Weke branch, Indomaret Weke branch, Kimia Farma Andi Makkasau Pharmacy, Kimia Farma Pharmacy, Bau Massepe Pharmacy, and Indah Farma Pharmacy. Interviews corroborated the findings. Additionally, this study utilized secondary data from Al-Gazali’s work Ihya Ulumiddin and contemporary research. More precisely, when the sickness struck, Al-Gazali’s beliefs acted as a check on capitalist behavior. The qadr al-hajah and ihsan were revealed to be the most critical aspects in encouraging sharing and caring while simultaneously minimizing panic buying and hoarding. This article is expected to contribute to the scientific riches of the Co-19 Era and to fill the moral hole produced by capitalism.